Pendidikan Gender: Kedudukan Ikhwan dan Akhwat Perspektif Hadis Shahih - Wisudatul Ummi Tanjung (Journal of Islamic Education Research, 2021)
Discussions relating to women are very important to be studied, so that there is no mistake in placing women's positions. This study aims to describe the equality between men and women. This type of study is library research by collecting secondary data and analyzed descriptively. The results of this study indicate that it is very important to understand and explore the meaning implied in the hadith, because otherwise a distorted understanding will arise.